The contact mechanics challenge: tribology meets soft matter. Issue 28 (4th July 2018) - Style, Robert W.; Krick, Brandon A.; Jensen, Katharine E.; Sawyer, W. Gregory
Abstract : In the fall of 2015, Martin Müser suggested a Contact Mechanics Challenge for the Tribology community. We review the results of the Contact Mechanics Challenge, and discuss how it highlights exciting opportunities for the Soft Matter community in Tribology, Surface Science, and Contact Mechanics. Abstract : In the fall of 2015, Martin Müser suggested a Contact Mechanics Challenge for the Tribology community. The challenge was an ambitious effort to compare a wide variety of theoretical and computational contact-mechanics approaches, and involved researchers voluntarily tackling the same hypothetical contact problem. The result is an impressive collection of innovative approaches – including a surprise experimental effort – that highlight the continuing importance of surface contact mechanics and the challenges of solving these large-scale problems. Here, we describe how the Contact Mechanics Challenge also reveals exciting opportunities for the Soft Matter community to engage intensely with classical and emerging problems in tribology, surface science, and contact mechanics.